2016
DOI: 10.1371/journal.pone.0166475
|View full text |Cite
|
Sign up to set email alerts
|

Meningococcal Carriage among Adolescents after Mass Meningococcal C Conjugate Vaccination Campaigns in Salvador, Brazil

Abstract: Neisseria meningitidis is a commensal bacterium of the human nasopharynx. In rare cases, it penetrates the mucosa, entering the blood stream and causing various forms of disease. Meningococcal conjugate vaccines can prevent invasive disease not only by direct effect in vaccinated individuals but also by herd protection, preventing acquisition of carriage, which interrupts transmission and leads to protection of unvaccinated persons. In 2010 in Salvador, Brazil, an outbreak of group C meningococcal disease led … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 38 publications
2
25
1
Order By: Relevance
“…North American and European studies have found an association between smoking and carriage [14,15], and a study from sub-Saharan Africa found an association between both passive and active smoking and carriage, the latter of which was statistically significant [12]. In comparison, our review found a significant association of carriage with passive smoking in only three studies from the Americas [33,35,42] and no significant association with active smoking.…”
Section: Discussioncontrasting
confidence: 62%
See 2 more Smart Citations
“…North American and European studies have found an association between smoking and carriage [14,15], and a study from sub-Saharan Africa found an association between both passive and active smoking and carriage, the latter of which was statistically significant [12]. In comparison, our review found a significant association of carriage with passive smoking in only three studies from the Americas [33,35,42] and no significant association with active smoking.…”
Section: Discussioncontrasting
confidence: 62%
“…1). Of these, 14 met the inclusion criteria and were included in the review, including seven studies from Brazil [33][34][35][36][37][38][39], three from Chile [40][41][42], and one each from Colombia [43], Cuba [32], Mexico [44], and Paraguay [45] (Fig. 2; Table 2).…”
Section: Literature Search Findings On Carriage In the Americasmentioning
confidence: 99%
See 1 more Smart Citation
“…30 Carriage studies performed in Brazil after the implementation of the MCC vaccination programme consistently found genogroup B strains as the most frequent groupable isolate emphasizing the need for continuous MD surveillance to detect changes in the incidence of MenB disease in the future. 31,32 Despite the declining incidence rates of Men B disease, currently at historical low levels, our epidemiological data showed that the highest burden of MenB disease is consistently observed in children younger than 5 years, particularly young infants. Incorporation of MenB recombinant protein vaccines into the national immunization programmes targeting infants, the age group with the highest incidence rates of IMD, in the region will depend on continuous surveillance to provide quality information to guide future vaccination strategies.…”
Section: Discussionmentioning
confidence: 73%
“…Up to now, many studies all over the world have investigated the asymptomatic carriage of N. meningitidis. Currently, the carriage rate in healthy populations is highly variable, and ranges from 0% to 30% worldwide [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. With regard to carriage according to age, teenagers have been found to have the highest carriage rate [5,7,10].…”
Section: Introductionmentioning
confidence: 99%